Promoting positive youth development and well-being: lesson learned from youth integrated health post in Indonesia - Yudanagara, Bani Bacan Hacantya; Surjaningrum, Endang Retno; Syamsir, Syamikar Baridwan (Intelektual Pustaka Media Utama, 2023)
Indonesia is a multicultural country with many indigenous people, including the Tengger tribe, who live in the mountainous area called Tosari. Limited access in rural areas and various risky behavior are the challenges for youth to develop optimally. To fill this gap, Tosari youth, together with midwives and the village office, initiated a youth-integrated health post called posyandu youth (PR), which was adapted to local culture. This study determined outcomes, program quality, and the possibility of PR program development using the positive youth development (PYD) framework. This study employed a qualitative design with a case study approach. From semi-structured interviews with various key stakeholders of PR, findings reveal a connection between the PR program quality and the positive health and well-being outcomes among participants. Based on these findings, several recommendations for maximizing PR as a youth development program to improve PYD and well-being among indigenous youth are provided.